How could hypoglycemia-inducing glycogen storage disease lead to hyperglycemia-induced mucormycosis? - Larry Nichols; Diana Alejandra Rios (University of São Paulo, 2020)
Mucormycosis is an increasingly frequent, difficult to diagnose, difficult to treat, often fatal infection, especially in patients with hyperglycemia from uncontrolled diabetes. Type I (von Gierke) glycogen storage disease is due to inherited deficiency of enzymes in glycogen metabolism, which causes hypoglycemia. This report is the case of a patient with von Gierke disease and a missed diagnosis of pulmonary mucormycosis. This report illustrates the importance of having a high index of suspicion for mucormycosis in the appropriate clinical context.